Spatial expression of two anti-inflammatory mediators, annexin 1 and galectin-1, in nasal polyposis - Sena, A. A. S.; Provazzi, P. J. S.; Fernandes, A. M.; Cury, P. M.; Rahal, Paula [UNESP]; Oliani, S. M. (Blackwell Publishing, 2006)
Background There is renewed interest in the role played by specific counter-regulatory mechanisms to control the inflammatory host response, poorly investigated in human pathology. Here, we monitored the expression of two anti-inflammatory mediators, annexin 1 and galectin-1, and assessed their potential link to glucocorticoids' (GCs) effective control of nasal polyposis (NP).Methods Total patterns of mRNA and protein expression were analysed by quantitative real-time PCR (qPCR) and Western blotting analyses, whereas ultrastructural immunocytochemistry was used for spatial localization and quantification of each mediator, focusing on mast cells, eosinophils and epithelial cells.Results Up-regulation of the annexin 1 gene, and down-regulation of galectin-1 gene, was detected in polypoid tissue compared with nasal mucosa. Patient treatment with betamethasone augmented galectin-1 protein expression in polyps. At the cellular level, control mast cells and eosinophils displayed higher annexin 1 expression, whereas marked galectin-1 immunolabelling was detected in the granule matrix of mast cells. Cells of glandular duct epithelium also displayed expression of both annexin 1 and galectin-1, augmented after treatment.Conclusion Mast cells and epithelial cells appeared to be pivotal cell types involved in the expression of both annexin 1 and galectin-1. It is possible that annexin 1 and galectin-1 could be functionally associated with a specific mechanism in NP and that GC exert at least part of their beneficial effects on the airway mucosa by up-regulating, in a specific cell target fashion, these anti-inflammatory agonists.
Keywords: annexin 1; epithelial cells; galectin-1; glucocorticoid; inflammatory cells; nasal polyp